Werkzeug- und Prozessentwicklung des Roll-to-Roll-Hochdurchsatzverfahrens zur kontinuierlichen, großflächigen Mikrostrukturierung - Striegel, Andreas Maximilian (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie, 2022)
This work describes the set-up of a roll-to-roll (R2R) system and the development of a specific microstructuring process for a variety of different materials ranging from high-performance polymers and low-melting-point metals to glass nanocomposites and thermoplastic nonwovens, including a lithography and electroplating-based semi-automated tooling production for seamless R2R microreplication.